Kemampuan Menyimak Teks Bahasa Jerman - Resiana Munda'; Hasmawati Hasmawati (Universitas Negeri Makassar, 2023)
Abstract. This study aims to determine the level of ability to listen to German language texts for class XII students at SMA Negeri 8 Makassar. This study uses a quantitative descriptive method. Data collection uses a written test or objective test which consists of multiple choice, true-false and questionnaire. Furthermore, the data were analyzed using percentage techniques. The population in this study were class XII students at SMA Negeri 8 Makassar, which consisted of 4 classes with 144 students. The sample of this research was students of class XII IPA 3 as many as 33 students who were selected using purposive sampling. The results of this study indicate that the ability to listen to German language texts for class XII students at SMA Negeri 8 Makassar is in the sufficient category (65%).Keyword: Language ability, Text, German Language